The isometric and isokinetic knee extension and flexion muscle strength profile of elite soccer players - Keytsman, C.; Verbrugghe, J.; Eijnde, B. O. (BMC Sports Science, Medicine and Rehabilitation, 2024)
Background This study aimed to further complete normative data sets for the strength profile of the thigh in soccer players by performing isometric and isokinetic measurements in a large sample per player position.